Necessity of Knowledge Management Practices in TVET Projects in Nepal - Adhikari, Devendra (Journal of Training and Development, 2020)
Unemployed youths in Nepal have been receiving vocational training through different projects with the support of international donor communities. Many of these projects simply meet their objectives by fulfilling the quotas of the training participants. There are some TVET projects in Nepal, which do not have priorities in sharing the learning and good practices that were gained during their implementation period due to the lack of Knowledge Management (KM) and disseminating mechanism. The purposes of this article are (i) to disseminate some activities and learnings gained by a Technical Education and Vocational Training (TVET) Project in Nepal which trained nearly 3000 youths from 2012-2016, and (ii) tracing out the importance of the KM practices in every TVET projects. This is a case study research in which secondary information such as the review of the project documents and the reflections of the author as a practitioner-scholar have been used as data. The findings of this research reveal that every TVET project in Nepal has gathered vast sources of knowledge and data. These learning will be beneficial to other forthcoming projects of similar nature. If these data and knowledge are shared among other TEVT project's, then huge financial resources of the state will also be saved. This research article could help us to consider about the importance of KM system in TVET projects.